THE ON-SCREEN EMBODYMENT OF FASHION: A VIEW FROM THE PROVINCES / ЭКРАННОЕ ВОПЛОЩЕНИЕ МОДЫ: ВЗГЛЯД ИЗ ПРОВИНЦИИ - SIYUKHOVA A.М. / СИЮХОВА А.М. (Наука телевидения)
The article examines the interaction of institutions of fashion in the context of screen culture. In the course of the sociological survey, conducted within the walls of the Maikop State Technological University, it was revealed that fashion screen broadcast has a beneficial effect on the bulk of the community, creating a psychological comfort and finding an effective way of formation and expression of personal identity.